2005
DOI: 10.1002/cphc.200400663
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Liquid Methanol

Abstract: A combination of density functional calculations of molecular clusters with a quantum cluster equilibrium (QCE) model provides evidence that liquid methanol is dominated by cyclic and/or lasso structures. Only cluster populations including these structures fit the measured thermodynamic and spectroscopic properties, such as heat of vaporization, heat capacity, NMR chemical shifts, and quadrupole coupling constants. On the other hand, cluster populations comprising open-chain structures fail to reach the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 54 publications
3
82
0
Order By: Relevance
“…Indeed, even the most elementary alcohol molecules, such as methanol and tert-butanol, are known to form a rich variety of clusters in the dense liquid, such as zigzag chains, loops, and lassos. 1,2 This has been confirmed both from spectroscopic sources 1,2 and computer simulations. [3][4][5][6][7] The microstructure of the archetype of associating liquids, namely, water, is still under debate: is it a network of H bonds 8 or a mixture of tetrahedrally rich and poor phases, 9,10 or eventually both?…”
Section: Introductionsupporting
confidence: 81%
“…Indeed, even the most elementary alcohol molecules, such as methanol and tert-butanol, are known to form a rich variety of clusters in the dense liquid, such as zigzag chains, loops, and lassos. 1,2 This has been confirmed both from spectroscopic sources 1,2 and computer simulations. [3][4][5][6][7] The microstructure of the archetype of associating liquids, namely, water, is still under debate: is it a network of H bonds 8 or a mixture of tetrahedrally rich and poor phases, 9,10 or eventually both?…”
Section: Introductionsupporting
confidence: 81%
“…The zig-zag characteristics of successively deuterated methanol's boiling points could be explained in terms of zero-point energy contributions [30,31]. Matisz et al confirmed the dominance of the cyclic methanol clusters [20].…”
Section: Introductionmentioning
confidence: 85%
“…Varying electronic structure but fixed MP2/TZVPP frequency and same a mf methanol: Ludwig studied the structure [30] and isotope effects [31] of liquid methanol and found mainly ring structures to constitute the liquid phase contrary to molecular dynamics simulations based on the pairwise additivity approximation. The zig-zag characteristics of successively deuterated methanol's boiling points could be explained in terms of zero-point energy contributions [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Furthermore, it has been demonstrated that the QCE offers an alternative to established methods concerning the investigation of thermodynamic data as well as structural aspects. [13][14][15] In his original paper, Weinhold described how the well-known rigid-rotor-harmonic-oscillator models may be employed for the analysis of condensed phases based on a distinct number of oligomers of the investigated substance.…”
Section: Introductionmentioning
confidence: 99%